Development Of Attitude Determination For Student Pico-Satellite INNOSAT. - M, Fadly; Sidek, Dr.Othman; Md Said, Md Azlin (2010)

(untitled)
Information of satellite’s attitude is very useful in autonomous satellite control system. For a small satellite particularly, attitude sensor cannot be installed in the satellite because of the limited weight and power consumption.